2007
DOI: 10.1007/s10460-007-9087-8
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the process of becoming a farm successor on Swiss family farms

Abstract: A theoretical model for farm succession is developed in which identity-related variables such as preferences for working autonomously or with animals influence occupational choice at the outset of the process, while environmental factors such as farm size and income prospects gain in importance during the latter stages of succession. A survey of 14-to-34-year-old potential farm successors in Switzerland is carried out to test the model. While female respondents focus on identity-related factors when making occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
4
26
0
2
Order By: Relevance
“…Some years ago, a quantitative study from Switzerland (Mann 2007a) tested and partly confirmed this model. Seven hundred and thirty-one children of farm managers aged between 14 and 35 years returned a questionnaire on their intention to take over the parental farm.…”
Section: Identity and Environmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Some years ago, a quantitative study from Switzerland (Mann 2007a) tested and partly confirmed this model. Seven hundred and thirty-one children of farm managers aged between 14 and 35 years returned a questionnaire on their intention to take over the parental farm.…”
Section: Identity and Environmentmentioning
confidence: 93%
“…One fringe result of the study referred to the gender aspect (Mann 2007a). The farm managers' daughters did not only respond in fewer numbers than the sons did, they also showed much less inclination to take over their parents' farm.…”
Section: Identity and Environmentmentioning
confidence: 94%
“…Para os jovens do Oeste de Santa Catarina , ser agricultor não é a expectativa profissional almejada. Mann (2007) evidencia, em seu estudo com jovens suíços, que os fatores ocupacionais de escolha profissional costumam ser ignorados. Segundo o autor, essa escolha é individual e tem significativa relação com o sexo (masculino ou feminino), com a idade e a escolaridade do jovem.…”
Section: Quadro 1 -Fatores Que Influenciam a Decisão Dos Jovens Em Saunclassified
“…Second, farmer or farm family factors, including personal preferences, values and/or intrinsic rewards (e.g., Dumas et al . ; Koch‐Achelpöhler ; Mann ), formal education levels (e.g., Kimhi and Nachlieli ; Hennessey and Rehmann ), practical skills and knowledge (e.g., Weiss ; Corsi ), and intergenerational relationships (e.g., Williams ; Brandth and Overrein ).…”
Section: The Need For a Socially Constructivist Understanding Of Famimentioning
confidence: 99%